Pendampingan Identifikasi Potensi Objek Wisata Pulau Semut dalam Perancangan Design Peta Wisata - Muthia Anggraini; Virgo Trisep Haris; Alfian Saleh (Faculty of Engineering, Universitas Semarang, 2024)
Indonesia is a country that has unique tourism potential areas. Semut Island is an ecotourism that is still beautiful with the development of a local community-based tourism sector. Access to tourist attraction locations is still unknown to many people around Pekanbaru City. For this reason, a map of tourist attraction locations is needed to make it easier for visitors to access tourist locations. Before a tourist map is created, it is necessary to identify potential tourist attractions in Semut Island. This activity aims to help partners identify the potential of the Semut Island tourist attraction. The method used is the discussion and mentoring method. As a result, partners were able to identify the potential of the Semut Island tourist attraction and were able to form a grand design for the Semut Island tourist attraction.